Changes in Behaviour and Proxies of Physiology Suggest Individual Variation in the Building of Migratory Phenotypes in Preparation for Long-Distance Flights - Handby, Tess; Slezacek, Julia; Lupi, Sara; Colhoun, Kendrew; Harrison, Xavier A.; Bearhop, Stuart (Frontiers in Ecology and Evolution, 2022)
Long distance migration in birds is a complex syndrome that involves high energy costs and, in some species, substantial physiological re-organisation. Such flexible migratory phenotypes are commonly associated with bird species flying non-stop across vast ecological barriers, where there are few opportunities to stop and refuel en route. Prior to making migratory flights, some species have been found to atrophy organs that are not required (e.g. digestive organs) and grow those associated with powering flight (pectora muscles and heart), presumably to optimise costs. However, most studies of this flexibility have required sacrificing study animals and this has limited our capacity to measure individual variation and its potential consequences. Here we investigate the behavioural and, indirectly, physiological adaptation of an arctic breeding long distance migrant the light-bellied brent goose Branta bernicla hrota, during spring staging in southwest Iceland. We use a sequential sampling approach to record behavioural observations and conduct stable isotope analysis of faecal samples from uniquely marked individuals to assess protein catabolism. Individuals showed a three-phase fuel deposition process, with initial slow intake rates followed by hyperphagia and then a period of inactivity immediately prior to migratory departure (despite multiple days with favourable wind conditions). The C:N ratio and δ15N values in faeces were significantly linked to fat deposition during the latter stages and suggests catabolism (reorganisation of proteins) occurring prior to departure. Our results suggest a strategic delay in migratory departure to enable reorganisation into a flying phenotype and that the extent of this varies among individuals. Further studies using ultrasonography techniques are warranted to support this sequential sampling technique and to understand the causes and consequences of variation among individuals.